Synthesis and Characterization of Optical Properties of Carbon Quantum Dots (CQD) Based on Mustard Green (Brassica juncea L) Leaf with Urea Addition - Yuniarti, Elvan; Nurlaela, Ai (Syarif Hidayatullah State Islamic University, 2023)
Carbon quantum dots (CQDs) are a class of fluorescent carbon nanomaterials. Carbon quantum dots (CQDs) were synthesized in this work from Mustard Leaves (Brassica juncea L) with the Addition of Urea via a microwave-assisted reflux method. This research aims to characterize CQDs' optical properties, energy gap, and emission under UV light computationally and experimentally. The studied optical properties obtained the maximum absorption peak observed from the UV-Vis spectrum of CQDs without urea shown at 233 nm. The UV-Vis spectrum of CQDs with the addition of urea (1 g, 1.5 g, and 2 g urea) has maximum absorption peaks at 424 nm, 422 nm, and 418 nm. The addition of urea causes a shift in the peak of the UV-Vis absorption spectrum towards red wavelengths (redshift). CQDs display bright green emissions when exposed to UV irradiation. In this work, the structures of CQDs of various forms (CQD-24, CQD-54, CQD-24-NH2, CQD-54-NH2) are theoretically studied in detail, and the results present both models (CQD-24, CQD-54) shows that the calculation results are in accordance with the experimental results, namely having a maximum UV-Vis absorption at 233 nm and in the range 200-400 nm. The results of calculations based on experiments show the same trend, namely that with the addition of urea, there is a shift in the absorption peak (redshift). The gap energy obtained also decreased with the addition of urea. CQDs solution emits yellow-green light.